Effects of Tai Chi-based cardiac rehabilitation on aerobic endurance, psychosocial well-being, and cardiovascular risk reduction among patients with coronary heart disease: A systematic review and meta-analysis. (1st April 2018) - Liu, Ting; Chan, Aileen W K; Liu, Yun Hong; Taylor-Piliae, Ruth E
Abstract: Introduction: Tai Chi is an attractive exercise to improve cardiovascular health. This review aimed to synthesize articles written both in Chinese and in English to evaluate the effects of Tai Chi-based cardiac rehabilitation on aerobic endurance, psychosocial well-being and cardiovascular diseases risk reduction for coronary heart diseases patients. Methods: PRISMA guidelines were used to search major health databases to identify randomized controlled trials or non-randomized controlled clinical trials that evaluated Tai Chi intervention compared with active or non-active control groups in coronary heart disease patients. When suitable, data were pooled using a random-effects meta-analysis model. Results: Thirteen studies met the inclusion criteria. Tai Chi groups showed a large and significant improvement in aerobic endurance compared with both active and non-active control interventions (standard mean difference (SMD) 1.12; 95% confidence interval (CI): 0.58–1.66; p <0.001). Tai Chi groups also showed a significantly lower level of anxiety (SMD=9.28; CI: 17.46–1.10; p =0.03) and depression (SMD=9.42; CI: 13.59–5.26; p <0.001), and significantly better quality of life (SMD=0.73; 95% CI: 0.39–1.08; p <0.001) compared with non-active control groups. Conclusion: Significant effects of Tai Chi have been found in improving aerobic endurance and psychosocial well-being among coronary heart disease patients. Tai Chi could be a cost-effective and safe exercise option in cardiac rehabilitation. However, the effect of Tai Chi on cardiovascular disease risk reduction has not been amply investigated among coronary heart disease patients. Caution is also warranted in view of a small number of studies for this meta-analysis and potential heterogeneity in differences in the varied designs of Tai Chi intervention.